2021
DOI: 10.5433/1679-0359.2021v42n4p2253
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of H2O2 as salt stress attenuator in ‘BRS Rubi do Cerrado’ sour passion fruit

Abstract: Irrigation with saline water causes a reduction in yield, especially in semi-arid regions. Cultivation strategies have been developed to mitigate salt stress on plants, such as the use of hydrogen peroxide. The objective of this study was to evaluate the attenuating effect of hydrogen peroxide on the gas exchange and growth of ‘BRS Rubi do Cerrado’ sour passion fruit cultivated under irrigation with saline water. The design was completely randomized in split-plot plots, with water salinity levels ECw (0.6, 1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The experimental design used was randomized blocks, in a 5 × 3 factorial arrangement, referring to five levels of electrical conductivity of water -ECw (0.3; 1.3; 2.3; 3.3 and 4.3 dS m -1 ) and three concentrations of hydrogen peroxide -H 2 O 2 (0, 25 and 50 μM) with five replicates and one plant per plot. Due to few studies with H 2 O 2 in vegetables, the concentrations used were based on studies carried out with zucchini (DANTAS et al, 2021), passion fruit (RAMOS et al 2021) and passion fruit (Silva et al, 2019), while salinity levels were based on SOARES et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…The experimental design used was randomized blocks, in a 5 × 3 factorial arrangement, referring to five levels of electrical conductivity of water -ECw (0.3; 1.3; 2.3; 3.3 and 4.3 dS m -1 ) and three concentrations of hydrogen peroxide -H 2 O 2 (0, 25 and 50 μM) with five replicates and one plant per plot. Due to few studies with H 2 O 2 in vegetables, the concentrations used were based on studies carried out with zucchini (DANTAS et al, 2021), passion fruit (RAMOS et al 2021) and passion fruit (Silva et al, 2019), while salinity levels were based on SOARES et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…Ramos et al [60] and Saddiq et al [61] studied the fluorescence of chlorophyll a in wheat leaves to verify the effects of salinity on PSII. They found that the rapid decline in photosynthesis under saline stress is reversible and specific for osmotic stress, where the slow decline is irreversible and specific to ionic stress.…”
Section: Chlorophyll Fluorescence Amentioning
confidence: 99%